Attitude, Motivation And Domains Of Use In English Language Learning: A Study Of Undergraduates In Kolej Universiti Islam Malaysia - Norhana Abdullah; Zarina Ashikin Zakaria (Universiti Sains Islam Malaysia, 2024)
This research identifies and analyzes the socio-psychological orientations of the undergraduate students of Kolej Universiti Islam Malaysia towards learning English. The study focuses on the two most important social psychological variables: attitude and motivation. Domain use is also investigated to find out the present linguistics reality of this group of undergraduates which features importantly in describing their motivational orientation. The research ultimately shows that this group of students focuses on English for its instrumental role in limited and discrete domain areas where knowledge of English is required, ultimately shaping their ideas about learning English. The study also suggests that among students with Islamic religious background English is very much domain specific and is used mainly for specific purposes. The use is especially restricted within the academic domain and is rarely extended to the communicative role of the language. This study of the social-psychological variables of the students will possibly provide additional insights in better identifying existing motivational challenges and in taking a more realistic perspective about the ELT (English Language Teaching) situation in the country. Finally, some considerations for ESP materials development and ELT approaches especially among young adult learners involved in Islamic based studies could be implied from the findings of the study.